TOWARDS AUTONOMY IN LANGUAGE LEARNING: THEORETICAL IMPLICATIONS AND PRACTICAL APPLICATIONS - Wade, John Christopher Christopher (Verbum, 2018)
It is the purpose of this paper to examine some aspects of autonomy in language learning with a specific focus on the transition from high school to the first year at university. This transition can be problematic, in that study at a university level requires a degree of independence and initiative which is not generally required in the supportive learning environment of the school system. Our starting point is identifying those characteristics which make a good language learner (Naiman et al. 1978; Johnson 2001; Maftoon and Seyyedrezaei 2012) and to demonstrate that these characteristics are largely an innate capacity of some and not all learners. Among these characteristics there is the ability to establish a systematic and autonomous approach to the learning process on the basis of personal inclinations and individual life-skills (Dublin Descriptors 2005). In this sense the good learner is not a passive participant in the process, but, as Schön (1987) claims, acts as a ‘problem-solver’, able to make decisions and put those decisions into practice. That is to say, learning is ‘the creation of knowledge’ (Kolb 1984). Finally, an approach to developing learner autonomy is illustrated, based on the personal experience of the author within the context of a first year ESP course in Communication Studies at the University of Cagliari (Italy). The course makes extensive use of the new technologies through a Moodle platform. It will be demonstrated that a blend of traditional teaching and e-learning can provide a ‘bridge’ between school and university, allowing the learner to move within a flexible environment and acquire the skills necessary for successful learning.